Literature Review on Factors Influencing Milk Purchase Behaviour - Kurajdova, Klaudia; Taborecka-Petrovicova, Janka (International Review of Management and Marketing, 2014)
In today’s highly informed, competitive and saturated market, a key to success of any business depends on knowing consumer and his consumption patterns and recognizing and understanding factors influencing his decision-making for the purpose of developing an attractive offer of products, supporting services, communication means and other marketing tools that would fit like a glue to customer’s needs. Study of consumer behaviour belongs to a group of very wide and strong subjects of marketing attention and its examination requires ongoing approach. Milk, as one category of dairy products, belongs to the group of basic daily-consumed products characterized by relatively high purchase frequency. On the other hand, its production and consumption is experiencing certain negative trend in Slovakia what inevitably calls for a scientific attention and examination in order to reverse this unfavourable development having a negative impact on the milk companies in Slovakia. Therefore, we focus our attention on studying various factors influencing consumers when purchasing this specific product. Our research in this stage resulted in the compilation of literature review on factors influencing consumers when purchasing milk and determination of boundaries and guidelines for our future research activity. Keywords: consumer behaviour; factors influencing milk purchase behaviour; milk. JEL Classification: M31